The Influence of the Use of Information Technology, Supervision and Audit, Use of Pnbp Funds, and Implementation of Sanctions on the Quality of Management of Non-Tax State Revenue in Ministry/State Agencie - Januar, Indra K; Sueb, Memed; Mulyani, Sri (Budapest International Research and Critics University, 2024)
Indonesian non-tax state revenue (PNBP) has an important and strategic role as one of the pillars of state finance in supporting government policies, controlling and supervising state resources. The form of implementing the PNBP regulatory function is very closely related to the regulations related to tariffs and the use of funds sourced from PNBP. In year 2022 The Audit Board of the Republic of Indonesia report, there are PNBP management problems that recur from year to year and challenges in PNBP management that are not yet effective and optimal, including there is levies that do not have a legal basis and the proceeds are used directly without being deposited into the state treasury first, levies already have a legal basis and the proceeds are used directly without being deposited into the state treasury first , and PNBP is late or not deposited into the state treasury or insufficient or not collected. SIMPONI application Information Systems that support the implementation of PNBP still experiences obstacles. There are five main new provisions in this regulation of PNBP funds, governance, supervision, sanctions and the right to pay. Therefore, research is needed to answer problems or phenomena that occur to be studied more deeply in order to achieve the goal, namely effective and efficient management of quality and fair PNBP in optimizing state revenues from the PNBP sector. Result show the influence of has a positive and significant effect on the Quality of PNBP Management in Ministries/State Institutions